2013
DOI: 10.1080/02755947.2013.824932
|View full text |Cite
|
Sign up to set email alerts
|

Venting and Reef Fish Survival: Perceptions and Participation Rates among Recreational Anglers in the Northern Gulf of Mexico

Abstract: Fisheries scientists, managers, and industry have developed innovative tools and techniques to improve the survival of fishes captured and released in deepwater settings. Venting involves the insertion of a hollow needle to deflate a fish's swim bladder and is among the most widely promoted barotrauma mitigation techniques. However, its efficacy has been the subject of intense debate. In the northern Gulf of Mexico, venting tools are mandatory tackle for offshore reef anglers, but current mandates on usage are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 21 publications
(26 reference statements)
3
30
0
Order By: Relevance
“…Similarly, recreational and tournament anglers in the northern Gulf of Mexico that were surveyed before removal of the venting tool requirement agreed that venting tools increase fish survival (Scyphers et al. ). Notably, this perception of positive impacts does not translate directly into the use of barotrauma mitigation.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, recreational and tournament anglers in the northern Gulf of Mexico that were surveyed before removal of the venting tool requirement agreed that venting tools increase fish survival (Scyphers et al. ). Notably, this perception of positive impacts does not translate directly into the use of barotrauma mitigation.…”
Section: Discussionmentioning
confidence: 97%
“…Although fishers in the survey were confident in their ability to use venting tools, previous research indicates that many fishers use improper venting techniques (Scyphers et al. ; Hazell et al. ) and that knowledge of proper venting methods is not linked to fishing experience (Scyphers et al.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One management strategy enacted by the GMFMC to increase survival in reef fish was a requirement to vent the swim bladder prior to release (GMFMC 2007). More recently, there has been some skepticism over the efficacy of venting in reducing discard mortality (Wilde 2009;Scyphers et al 2013;Campbell et al 2014), and studies specific to Red Snapper have shown positive (Gitschlag and Renaud 1994), neutral Wilson 1994, 1996), and negative (Burns et al 2002) effects of venting on survival. An alternative to venting, and potentially a more effective release method, is rapid recompression using descender devices.…”
mentioning
confidence: 99%
“…A central objective of our study was to understand the underlying drivers of support for management and stewardship initiatives, which can be influenced by numerous socioeconomic, cultural, and political factors and experiences (e.g., Cinner 2005, McClanahan et al 2005, Gelcich et al 2008, Scyphers et al 2013. The most common and recently proposed initiatives for oysters have included reducing fishing pressure, increasing habitat availability, developing spawning sanctuaries and MPAs, increasing educational outreach, and improving management of freshwater and pollution inflows.…”
Section: Discussionmentioning
confidence: 99%